2020
DOI: 10.24996/ijs.2020.61.7.25
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stage Social Friend Recommendation System Based on User Interests

Abstract: The use of online social network (OSN) has become essential to humans' lives whether for entertainment, business or shopping. This increasing use of OSN motivates designing and implementing special systems that use OSN users' data to provide better user experience using machine learning and data mining algorithms and techniques. One system that is used extensively for this purpose is friend recommendation system (FRS) in which it recommends users to other users in professional or entertaining online social net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In 2020, Qader et al [11] suggested a Dual-Stage FR model to recommends users to other users based on user interests. The model applies the double stage technique on unlabeled information of 1241 users collected from OSN users via the online survey.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2020, Qader et al [11] suggested a Dual-Stage FR model to recommends users to other users based on user interests. The model applies the double stage technique on unlabeled information of 1241 users collected from OSN users via the online survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That indicates 97% users on our dataset are recommended accurately by our proposed system. Moreover, to compare the proposed model with other existing methods, we have re-implemented the models used in [8,10,11,12,13,14,16] as accordance with the description in the paper to make a fair comparison. All the models are evaluated on the same data set to ensure the fairness of the comparison.…”
Section: Precision Valuementioning
confidence: 99%
See 2 more Smart Citations
“…The study utilizes datasets sourced from the same opensource project as Eclipse. A recommendation engine [5][6][7] is employed, incorporating optimization techniques through utilizing various machine learning algorithms, including C4.5, neural networks, deep learning architectures, and optimization techniques using the most recent evolutionary algorithm. Several researchers utilized support vector machines and explored the application of unsupervised learning techniques.…”
Section: Introductionmentioning
confidence: 99%